Secure attachment predicts lower societal cost amongst severely antisocial adolescents - Christian J Bachmann; Sajid Humayun; Madeleine Stevens; Thomas G O'Connor; Stephen Scott (BMC, 2023)
Abstract Background Social and economic costs associated with antisocial behaviour are well-established, but little is known about the potential costs savings/benefits of secure attachment in this high-risk group. We aimed to provide the first test of attachment quality as a distinct predictor of economic costs. Methods 111 adolescents (10-17 years of age, M = 15.0, SD = 1.6; 71% male) referred to young offender services due to high levels of antisocial behaviour were included. Costs were measured by detailed service-use interview, and attachment security to mother and father elicited through the Child Attachment Interview. The level of antisocial behaviour and callous-unemotional traits were assessed. Cost predictors were calculated using generalised linear models. Results Mean 12-months service costs were £5,368 (sd 5,769) per adolescent, with justice system and educational service costs being the main components. After adjusting for covariates, economic costs were predicted by attachment quality to fathers, with a difference of £2,655 per year between those with secure (£3,338) versus insecure attachment (£5,993); significant cost effects were not found for attachment quality to mothers. Higher levels of callous-unemotional traits, lower verbal IQ, higher levels of antisocial behaviour, and older age were also significant cost predictors. Conclusions Secure attachment to fathers is a predictor of reduced public cost in adolescents with severe antisocial behaviour. This novel finding for severely antisocial youth extends previous findings in less antisocial children and underscores the public health and policy benefits of good caregiving quality and the value of population-level dissemination of evidence-based interventions that improve caregiving quality.